Angle-resolved photoemission spectroscopy on high-temperature superconductors : studies of Bi2212 and single-layer FeSe Film grown on SrTiO3 substrate /: studies of Bi2212 and single-layer FeSe Film grown on SrTiO3 substrate. (2016) - He, Junfeng
No abstract available